Development of Arduino-Based Electrical Practicum e-Module - Matsun Matsun; Soka Hadiati; Adi Pramuda (Radiasi : Jurnal Berkala Pendidikan Fisika, 2021)
The development of IoT-based innovative learning media to improve student competence is needed in the era of industrial revolution 4.0. This study aims to develop an electrical practicum e-module using the Arduino Uno experimental tool to get valid, practical, and effective criteria. The research method uses R&D with four D models. The development stage consists of the stages of defining, designing, developing, and limited dissemination. Data analysis used descriptive analysis with Aiken V. The results showed that the e-module get the criteria of high validity with index V = 0.87. 60% of the total number of students responded positively to the media, and 40% were very active when using the media, so the modules developed were considered practical. The effectiveness level of the module shows that 100% of the students get a higher learning outcome value than the learning completeness score, so it can be concluded that the e-module has met the effective criteria.